3D Flow Prediction for high rise structures - Leela, D; S, Babu; A K, Dasarathy; Kumar, S (International Journal of Engineering and Technology, 2018)
Structures more than 40 m are usually termed as high rise structures. It is difficult to predict the flow of wind around structures without the use of computational fluid dynamics software or wind tunnel. These high rise structures are subjected to stronger winds that can cause them to sway. So the predictions of aerodynamic loads acting on tall buildings are very important. This study aims to identify the characteristics of wind flow such high rise structuresÂ  by predicting flow variables such as pressure, velocity and impacting stress etc using Ansys Fluent 18.1. The main purpose of this project is to find out : pressure around the building and velocity of wind around the building.